Peran Sistem Hukum Terhadap Fenomena Hate Speech Politik Pada Generasi Muda di Media Sosial - Muhammad Ridhoni Azhary; Novita Khumaira; Siti Soleha Tiara Handraini; Didi Prahasto; M. Yanuar Rizali Khairullah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The development of social media has created an increasingly open digital communication space for young people to express their political opinions. However, this openness has also led to the growing phenomenon of political hate speech, especially during national political moments such as general elections and presidential elections. This study aims to analyze the role of the legal system in addressing the phenomenon of political hate speech among young people on social media and to identify forms of legal protection against the spread of hate speech in digital spaces. This research uses a normative legal research method with statutory and conceptual approaches. Legal materials were obtained from laws and regulations, scientific journals, books, and literature related to political hate speech on social media. The results of the study indicate that political hate speech is influenced by low digital literacy, political polarization, the spread of hoaxes, and the weak legal awareness of young people in using social media. The legal system in Indonesia, through Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016, the Criminal Code (KUHP), and the Chief of Police Circular Letter Number SE/6/X/2015 concerning the Handling of Hate Speech, has provided a legal basis for addressing hate speech on social media. However, the implementation of the law still faces various obstacles, such as multiple interpretations of regulations, weak digital legal education, and the rapid spread of information on social media. Therefore, synergy between the government, educational institutions, and society is needed to improve digital literacy and legal awareness among young people in order to create a healthy and democratic digital space.